The Organization of Sport Tourism of the Volyn Regional Centre of Tourism, Sports and Travelling Tours - Olena Demyanchuk; Iryna Erko; Ninel Matskevych; Vasyl Voitovych (Lesya Ukrainka Volyn National University, 2017)
The article deals with an overall analysis of legislative documents, research and methodological literature, the reports of the regional Centre of Tourism, Sports an Travelling tours as well as the published materials related to the out-of-school activities in the Volyn Region. Under consideration are state-level regulatory aspects of the tourism ethnography job in out-of-school institutions of Ukraine. The job in the field of Sport Tourism of Ukraine is headed by the Ukrainian State Centre of Tourism and Ethnography. This company serves the interests of the schoolchildren And is subordinated to the Ministry of Education and Science. The Centre of Tourism, Sports and Travelling Tours (functioning in the framework of the Volyn State Administration) is the most important out-of-school institution and coordinator of the tourist-ethnographic work in Volyn Region and one of the most prominent agencies in the fields of tourism for Ukrainian children and adolescents. Of great importance for the development of sport tourism and ethnography in Volyn region is the interest clubs operating in the Regional Centre of Sports and Travelling Tours. The number of those interest clubs and hobby groups is fairly considerable. The replies of the respondents of a poll demonstrate the children's participation in different sport tourists clubs of Volyn Region with the emphasis on a specific variety of tourism. The article contains the analysis of the major professional fields of the Agency: sport orienteering; sport tourists; geographic ethnography; geological ethnography; project of sport orienteering; project «A Wandering Mr.Know-All»; the project of «Tourism for Everyone»; Young Tourists as Ethnographers; historical Ethnography. The natural environment and resources of the Volyn region are quite propitious for the development of the touristethnographic and sport-tourist activity of the young people. The region offers very good opportunities for arranging walking and hiking tours, contests and just a recreation in the lap of nature. The contents of the activities of a typical interest club have been studied (the focus is on its resources and conditions). The task of our research is to analyze the peculiarities of the job of the tourist society as well as the problems it may face with. The accumulated knowledge, experience, the adequate organization and careful planning of the Centre's job will make it possible to upgrade the training the tourist staff, encourage the schoolchildren to participate in large-scale tourist events, contests, travelling tours.